Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18042078
|View full text |Cite
|
Sign up to set email alerts
|

Serum KL-6 Could Represent a Reliable Indicator of Unfavourable Outcome in Patients with COVID-19 Pneumonia

Abstract: KL-6 is a sialoglycoprotein antigen which proved elevated in the serum of patients with different interstitial lung diseases, especially in those with a poorer outcome. Given that interstitial pneumonia is the most common presentation of SARS-CoV2 infection, we evaluated the prognostic role of KL-6 in patients with COVID-19 pneumonia. Patients with COVID-19 pneumonia were prospectively enrolled. Blood samples were collected at the time of enrolment (TOE) and on day 7 (T1). Serum KL-6 concentrations were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…KL‐6 was measured by 90.3% of mild‐to‐moderate cases, and 96.3% of severe cases, suggesting that the effect of selection bias is very small. Several studies suggest that KL‐6 is a useful biomarker for predicting the severity of COVID‐19 and death 31,32 , which also supports the present results.…”
Section: Discussionsupporting
confidence: 90%
“…KL‐6 was measured by 90.3% of mild‐to‐moderate cases, and 96.3% of severe cases, suggesting that the effect of selection bias is very small. Several studies suggest that KL‐6 is a useful biomarker for predicting the severity of COVID‐19 and death 31,32 , which also supports the present results.…”
Section: Discussionsupporting
confidence: 90%
“…The clinical implications of serum KL‐6 and SP‐D levels have been investigated in the above‐stated context. As per reports, both serum KL‐6 and SP‐D levels are elevated in patients with severe COVID‐19 and, therefore, these constituents are useful biomarkers of disease severity 9,11,13,20,21 . In addition to disease severity, serum KL‐6 was reported to predict pulmonary fibrosis followed by infection with SARS‐CoV‐2 10,22 and serum SP‐D was reported to be useful for distinguishing pandemic influenza A (H1N1) from COVID‐19 in patients who required mechanical ventilation 23 .…”
Section: Discussionmentioning
confidence: 79%
“…The full text of 33 remained studies was assessed for eligibility and 12 case reports or case series ( Horii et al, 2020 ; Inoue et al, 2020 ; Ito et al, 2020 ; Nakamura et al, 2020 ; Scarpati, 2020 , Shibata et al, 2020 ; Shimazu et al, 2020 ; Zeng et al, 2020a ; Fukada et al, 2021 ; Sumimoto et al, 2021 ; Suzuki et al, 2021 ; Yamaya et al, 2021 ), 2 studies that did not report the results clearly ( Miyagami et al, 2021 ; Takeshita et al, 2021 ), 3 studies that did not classify patients based on disease severity ( Frix et al, 2020 ; Chen et al, 2021a ; Scotto et al, 2021 ) and 1 preprint study ( Alimova et al, 2020 ) were excluded. Finally, 15 studies identified as relevant and entered the quality assessment ( Awano et al, 2020 , d'Alessandro et al, 2020a , d'Alessandro and Cameli, 2020 , d'Alessandro et al, 2020b ; Frix et al, 2020 ; jp, 2020 , Saito et al, 2020 ; Wang et al, 2020 ; Xue et al, 2020 ; Anai et al, 2021 ; Bergantini et al, 2021 ; Chen et al, 2021 , d’Alessandro et al, 2021 ; Deng et al, 2021 ; He et al, 2021 ; Peng et al, 2021 ; Scotto et al, 2021 ). Ultimately, 7 studies (1 cross-sectional and 6 case-control studies) met the inclusion criteria of this systematic review ( Awano et al, 2020 , d'Alessandro et al, 2020b ; Saito et al, 2020 ; Bergantini et al, 2021 ; Deng et al, 2021 ; He et al, 2021 ; Peng et al, 2021 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%